Fuzz [compact disc, unabridged] : when nature breaks the law - Roach, Mary (Brilliance Audio, Inc., 2021)
What's to be done about a jaywalking moose? A grizzly bear caught breaking and entering? A murderous tree? As New York Times best-selling author Mary Roach discovers, the answers are best found not in jurisprudence but in science: the curious science of human-wildlife conflict, a discipline at the crossroads of human behavior and wildlife biology. Roach tags along with animal attack forensics investigators, human-elephant conflict specialists, bear managers, and 'danger tree' faller-blasters. She travels from leopard-terrorized hamlets in the Indian Himalaya to St. Peter's Square in the early hours before the Pope arrives for Easter Mass, when vandal gulls swoop in to destroy the elaborate floral display. Along the way, Roach reveals as much about humanity as about nature's lawbreakers. Combining little-known forensic science and conservation genetics with a motley cast of laser scarecrows, langur impersonators, and mugging macaques, Roach offers hope for compassionate coexistence in an ever-expanding human habitat.